Cost calculation and analysis in power generation enterprises - Urmanbekova Iroda Farkhodovna (Zien Journals, 2022)
The article examines the calculation and analysis of costs in power generation enterprises, in which products are one of the most important quality indicators, reflecting the results of economic activity of the enterprise, the technical and economic level of productionthe calculation of the unit of works, services and all products sold, the object of calculation, the unit of calculation, its types are covered. At the same time, the economic elements of the costs that make up the cost of production and the calculation items are disclosed on the basis of data from the joint-stock company "Fergana Thermal Power Plant"
Keywords: electric power; energy; production; product cost